The Examination of Effects of Cognitive Group Counseling on the Anxiety and Depression Factors in Female Senior Citizens Staying at Nursing Homes in Sabzevar in 2008-2009 - Abolghasem Khoshkonesh; Ebrahim Taghi Pour; Esmaeil Bashiri (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The main goal of this study is to determine the effect of cognitive group counseling on the anxiety and depression factors in female senior citizens staying at nursing homes. Methods & Materials: The method used in this pilot study is the pre-test and post -test with a control group and the statistical society in this study consists of all the elder women staying at Madar Nursing Home in Sabzevar. The sample was selected randomly from the society under study. The General Health Questionnaire (GHQ) was primarily administered and then scores higher than six for anxiety and depression factors were identified and a number of 30 subjects were selected randomly. Next, they were placed in two groups consisting of 15 subjects (subject group and control group). Results: The analysis of the results was performed using the covariance analysis. It indicates that cognitive group counseling significantly results in reducing depression and anxiety. Conclusion: Cognitive group counseling has a positive effect on reducing anxiety and depression. Refresher courses for the staff and nurses working in the nursing homes can serve as a supplementary treatment along with pharmaceutical treatment.